Exploring the Impact of Educational Interventions on Contact Lens Hygiene Practices among Medical and Non-Medical Students - Aslam, Muhammad Waseem; Irshad, Asima; Hassan, Faiza (Medical Journal of South Punjab, 2024)
Objective: To explore the impact of educational interventions on contact lens hygiene practices among medical and non-medical students.Methodology: This comparative cross-sectional study was conducted at Superior University and the University of Lahore (UOL) with a sample of 377 students aged 18-24, selected via non-probability convenient sampling from September 2023 to January 2024. Data on contact lens hygiene, wearing habits, and related knowledge were collected using a self-designed questionnaire and analyzed using SPSS version 25. Descriptive statistics and Chi-square tests were used, with a significance level of P